Pengembangan E-modul Pembelajaran Analisis Aliran Daya dengan Software ETAP pada Mata Kuliah Analisa Sistem Tenaga - Intan Sani, Aprilia; Agus Adiarta; I Gede Surya Bumi Pracasitaram (Jurnal Pendidikan Teknik Elektro Undiksha, 2024)
The study that will be discussed is a development in producing digital learning media, in the form of an effective e-module with discussion material on Power Flow Analysis in the course of Power System Analys in the Bachelor of Electrical Engineering Education study program at Ganesha University of Education. The method for processing the data obtained later that will be used in this activity are using statistical evaluation which will produce scores in the form of percentages either from content or material expert evaluations, media expert evaluations, and using questionnaires for testing on students. So the value that will be obtained from the validation test by content experts with percentage that the value of 97.5% that qualification range in the very feasible range, while the value obtained during the validation test by a media expert is inside the shape of a percentage with avalue of 97.5% with very worthy qualifications. The absolut consequences of testing on a small institution involving 5 respondents, and continued testing on a large group involving 15 respondents received scores that reach strongly agree category. From this explanation, an be concluded that the learning media whic is made in the form of a Power Flow Analysis E-Module is suitable for use when studying teaching activities in the Power System Analysis course at Ganesha University of Education Electrical Engineering Education Bachelor's study program.